Fintech Adoption Dynamics in Morocco and their Implications for Organisational Performance and Financial Market Responsiveness - Ennouhi, Zakaria; Lakrarsi, Abdelhalim (International Journal of Economics and Financial Issues, 2025)
This study investigates the determinants and consequences of financial technology adoption within the Moroccan context, with a particular focus on its role and contribution to organisational performance and financial market reactions. Relying on structural equation modelling, our analysis is based on data collected from a sample composed of various profiles, notably professionals. The conceptual model integrates technological, psychological and structural variables, stakeholder involvement, and risk perception. The results support the importance of all the endogenous variables and their influences on the adoption of technological innovations, with significant P values. In fact, the involvement of stakeholders emerged as the most critical determinant, with a path coefficient of 0.825 and a highly significant P value of 0.000, confirming the strength of this relationship. On the other hand, risk perception had no significant effect on fintech adoption, with a P value of 0.272, which is statistically above the significance threshold. Conversely, fintech adoption has a highly significant and positive effect on both organisational performance and financial market reactions, confirming its strategic role in creating value and improving competitiveness. These results highlight that integrating fintech depends on an innovative and structured ecosystem, whereas cybersecurity and regulation remain essential, although perceived risk is not a fundamental barrier in the context studied.